(untitled) (Faculty of Education Scientific Journal, 2024)
In this paper, The existence and uniqueness of solution is studied in L2[a,b]× L2[c,d]. Moreover, we use a degenerate kernel method to transform the integral equation into a linear algebraic system. In addition, the existence and uniqueness of this linear algebraic is discussed. Finally, numerical examples are considered and the error, in each case is computed by Maple.